Significance of Vascular Dipeptidyl Peptidase-4 Inhibition on Vascular Protection in Zucker Diabetic Fatty Rats - Shinji Takai; Hiroshi Sakonjo; Denan Jin (Elsevier, 2014)
Abstract.: To clarify the role of dipeptidyl peptidase-4 (DPP-4) inhibition in vascular tissues, we compared the effects of the poorly tissue-penetrative DPP-4 inhibitor sitagliptin to the highly tissue-penetrative DPP-4 inhibitor linagliptin in Zucker diabetic fatty (ZDF) rats. Six-week-old ZDF rats were orally treated with placebo, sitagliptin (10 mg/kg), or linagliptin (3 mg/kg) for 4 weeks. Sitagliptin and linagliptin produced equivalent decreases in blood glucose concentrations and increased plasma insulin concentrations during oral glucose tolerance tests after the first and the last treatments. In isolated arteries, acetylcholine-induced vascular relaxation was significantly augmented by sitagliptin and linagliptin, with significantly stronger relaxation observed with linagliptin compared to sitagliptin. Vascular DPP-4 activity was attenuated by these drugs, with linagliptin producing significant greater attenuation than sitagliptin. Vascular malondialdehide levels were significantly lower with linagliptin compared to sitagliptin. Significantly greater attenuation of vascular gene expressions of p22phox and monocyte chemoattractant protein-1 by linagliptin, compared with sitagliptin, was also observed. In conclusion, the superior vascular protection by linagliptin compared with sitagliptin was unrelated to the regulation of circulating glucose and insulin levels, and the stronger vascular DPP-4 inhibition by linagliptin may contribute to the mechanism of vascular protection. Keywords:: diabetes, dipeptidyl peptidase 4, inhibitor, vascular tissue, penetration